Kinetics and Mechanism of Oxidation of Aspartic Acid in Acid Solution of N-Bromosuccinimide in Presence of Iridium(III) - SINGH, A.K. (Asian Journal of Chemistry, 2010)
Kinetics and mechanism of iridium(III) catalyzed oxidation of aspartic acid by N-bromosuccinimide have been extensively studied under isolation condition at 30oC. The observed kinetic findings indicate first order reaction kinetics with respect to oxidant catalyst and chloride ion in each case, whereas it shows zero order reaction kinetics with respect to substrate and reductant. Successive addition of succinimide in the reaction system shows negative effect whereas addition of Hg(OAc)2 shows negligible efect on reaction rate. Insignificant effect of ionic strength of the media is observed in the oxidation reaction. On the basis of the experimental findings, the